2017
DOI: 10.4254/wjh.v9.i17.757
|View full text |Cite
|
Sign up to set email alerts
|

Liver immunology and herbal treatment

Abstract: Beyond the metabolic functions, the liver recently has been defined as an organ of immune system (IS), which have central regulatory role for innate and adaptive immunity. The liver keeps a delicate balance between hepatic screening of pathogenic antigens and immune tolerance to self-antigens. Herbal treatments with immunological effects have potential to alter this hepatic immune balance towards either therapeutic side or diseases side by inducing liver injury via hepatotoxicity or initiation of autoimmune di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…In this study, we found that AS-IV pretreatment (20 and 40 mg/kg) remarkably ameliorated APAP-induced liver injury, as evidenced by the reduced elevation of ALT and AST ( Figure 2 ), and the alleviated histological abnormalities ( Figure 3 ). There are an increasing number of studies showing that herbal medicines derived from plant extracts are being increasingly utilized to treat liver injury [ 14 , 15 ]. Plant extracts contribute to a variety of intracellular signaling cascades in hepatocyte to ameliorate inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that AS-IV pretreatment (20 and 40 mg/kg) remarkably ameliorated APAP-induced liver injury, as evidenced by the reduced elevation of ALT and AST ( Figure 2 ), and the alleviated histological abnormalities ( Figure 3 ). There are an increasing number of studies showing that herbal medicines derived from plant extracts are being increasingly utilized to treat liver injury [ 14 , 15 ]. Plant extracts contribute to a variety of intracellular signaling cascades in hepatocyte to ameliorate inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“… 24 GSH is the major nonenzymatic antioxidant and regulator of intracellular redox homeostasis in all cell types. 25 , 26 GSH depletion can increase the formation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) such as superoxide anion, hydroxyl radical, and hydrogen peroxide and nitro oxide. Additional levels of ROS and RNS can attack biological molecules such as DNA, protein, which leads to lipid peroxidation, and depletion of the antioxidant enzymes that later cause severe oxidative stress, DNA strand breaks, apoptosis, and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, silymarin has been found to significantly promote the survival period of alcoholic cirrhosis patients (139, 140). Further mechanism study indicated that flavonoids from Silybum marianum , including silybin and silymarin, could normalize immunoregulatory defects via restorating the cellular thiol status, inducing T-cell activation (CD69) with a significant reduction of TNF (139, 141). Although there is still a long way to go to fulfill the immunity treatment in ALD, it represents a very encouraging field for ALD therapy.…”
Section: Potential Therapeutic Approaches To Treat Ald Via Regulationmentioning
confidence: 99%